Tom and Rose Archuleta (Cimarron Legend, 1992)
Article is about the Archuleta family living in Cimarron, New Mexico.
Newspaper clipping and photograph of Tom, Rose and Christa Archuleta
Mater List Item # 12
File location is in the New Mexico File Cabinets
Keywords: Archuleta, Tom; Archuleta, Rose; Archuleta, Christa; Archuleta, Michelle; Pacific Stud -- Lumber yards; Life and Custums; Renovations; Family life; Cimarron, New Mexico; Denver, Colorado